2009
DOI: 10.1105/tpc.108.064667
|View full text |Cite
|
Sign up to set email alerts
|

Pentatricopeptide Repeat Proteins with the DYW Motif Have Distinct Molecular Functions in RNA Editing and RNA Cleavage in Arabidopsis Chloroplasts

Abstract: The plant-specific DYW subclass of pentatricopeptide repeat proteins has been postulated to be involved in RNA editing of organelle transcripts. We discovered that the DYW proteins CHLORORESPIRATORY REDUCTION22 (CRR22) and CRR28 are required for editing of multiple plastid transcripts but that their DYW motifs are dispensable for editing activity in vivo. Replacement of the DYW motifs of CRR22 and CRR28 by that of CRR2, which has been shown to be capable of endonucleolytic cleavage, blocks the editing activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
281
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(294 citation statements)
references
References 53 publications
12
281
1
Order By: Relevance
“…Fisk et al (1999) first reported a maize PPR gene, (for CHLOROPLAST RNA PROCESSING1), which was implicated by genetic analysis in processing and translation of plastid pet transcripts. Similar effects on plastid transcripts were subsequently observed in other mutants from Arabidopsis (Hashimoto et al, 2003;Meierhoff et al, 2003;Yamazaki et al, 2004;ChateignerBoutin et al, 2008ChateignerBoutin et al, , 2011Chi et al, 2008;Okuda et al, 2009Okuda et al, , 2010Yu et al, 2009;Johnson et al, 2010), rice (Kazama and Toriyama, 2003;Komori et al, 2004;Gothandam et al, 2005), and maize (Williams and Barkan, 2003;Schmitz-Linneweber et al, 2006;Pfalz et al, 2009;Prikryl et al, 2011). Additional evidence for a role of PPR proteins in regulating organelle gene expression has also come from positional cloning of several cytoplasmic male sterility (CMS) restorer genes from petunia (Petunia hybrida; Bentolila et al, 2002) and radish (Raphanus sativus; Brown et al, 2003;Desloire et al, 2003;Koizuka et al, 2003).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Fisk et al (1999) first reported a maize PPR gene, (for CHLOROPLAST RNA PROCESSING1), which was implicated by genetic analysis in processing and translation of plastid pet transcripts. Similar effects on plastid transcripts were subsequently observed in other mutants from Arabidopsis (Hashimoto et al, 2003;Meierhoff et al, 2003;Yamazaki et al, 2004;ChateignerBoutin et al, 2008ChateignerBoutin et al, , 2011Chi et al, 2008;Okuda et al, 2009Okuda et al, , 2010Yu et al, 2009;Johnson et al, 2010), rice (Kazama and Toriyama, 2003;Komori et al, 2004;Gothandam et al, 2005), and maize (Williams and Barkan, 2003;Schmitz-Linneweber et al, 2006;Pfalz et al, 2009;Prikryl et al, 2011). Additional evidence for a role of PPR proteins in regulating organelle gene expression has also come from positional cloning of several cytoplasmic male sterility (CMS) restorer genes from petunia (Petunia hybrida; Bentolila et al, 2002) and radish (Raphanus sativus; Brown et al, 2003;Desloire et al, 2003;Koizuka et al, 2003).…”
mentioning
confidence: 67%
“…Attempts to identify the in vivo RNA ligands have only been made for a few PPR proteins (Schmitz-Linneweber and Small, 2008;Okuda et al, 2009Okuda et al, , 2010Pfalz et al, 2009;Yu et al, 2009;Johnson et al, 2010;Chateigner-Boutin et al, 2011;Prikryl et al, 2011). Many of the postulated activities of PPR proteins still lack direct biochemical proof and thus leave open the possibility that their roles are more indirect than suspected and may require additional, unidentified factors.…”
Section: Ysa Encodes a Ppr Protein Essential For Chloroplast Biogenesmentioning
confidence: 99%
“…Contrary to this theoretical consideration, the two plastid RNA editing trans-factors CRR22 and CRR28 are still fully functional without their C-terminal DYW domain [8]. The DYW domain in MEF1 may be more important, since already the mutation of a single nucleotide in the EMS-line mef1-2 completely abolishes editing at two of the three target sites, rps4-956 and nad7-963, and results in a strong reduction at nad2-1160 [11].…”
Section: The Dyw Domain Is Necessary For Efficient Function Of Mef1mentioning
confidence: 81%
“…Concerning the cis-elements around the editing sites, a region between 20 nts upstream and only 3 nts downstream appears to be sufficient to identify a C-nucleotide target [3][4][5]. For the RNA editing in plastids several trans-factors have already been identified during the last few years [6][7][8][9][10], while the first trans-factors acting in mitochondria have been identified only recently [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the enzyme catalyzing the editing reaction, presumably by deamination, is still unknown, although suspicion has fallen on the DYW domain present in some PPR proteins because it contains residues similar to the conserved cytidine deaminase motif (15). The elusiveness of the enzyme responsible for plant RNA editing (16)(17)(18) suggests that some important components of the editing machinery are still to be identified.…”
mentioning
confidence: 99%